Price Discovery of Agri Commodities: An Integrated Approach - A. Mishra; R. P. Kumar (Финансы: теория и практика, 2022)
The purpose of this paper is to examine how the introduction of the pan-India electronic trading portal (eNAM) impacted the information transmission and price discovery in informationally linked markets of India for agricultural commodities. We have applied the information share and component share methods using daily data of five agricultural commodities from 2005 to 2019. This paper offers two findings, first; evidence shows that commodity stock prices have more price discovery as compared to the market prices. Whereas market prices also generate a significant price discovery, but its volume is less. Second, market prices adjust more quickly than commodity stock prices to correct the disproportion between both markets. This scenario is more evident post eNAM era. Conclusions from this study can be used to understand the information flow and would be helpful to academicians, practitioners, policymakers, or business players of commodity markets.